2018
DOI: 10.1371/journal.pone.0206937
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of commercial electronic nicotine delivery systems (ENDS) temperature control technology

Abstract: ObjectivesFor electronic nicotine delivery systems (ENDS), also commonly called e-cigarettes, coil temperature is a factor in the potential production of toxic chemical constituents. However, data are lacking regarding the temperatures that are achieved in the latest generation of these devices. Fourth-generation ENDS are capable of producing heating coil temperatures well above e-liquid boiling points, and allow the user to monitor and set the heating coil temperature during a puff. In this study, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 17 publications
3
29
1
1
Order By: Relevance
“…The potential of the identified metals and ceramics to catalyze harmful VEA reactions or aerosolize is dependent on the internal device temperatures achieved in actual usage [ 5 , 13 , 15 , 23 ]. Previous studies have reported typical 100–400°C wetted coil temperatures, depending on the device design, flow conditions, voltage, and measurement position relative to the coil [ 10 , 11 , 17 18 ]. Temperatures as high as 1,000°C have been measured for “dry” coils without any e-liquid, so efficient wicking is important for delivering liquid to the coil and maintaining target coil temperatures [ 10 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of the identified metals and ceramics to catalyze harmful VEA reactions or aerosolize is dependent on the internal device temperatures achieved in actual usage [ 5 , 13 , 15 , 23 ]. Previous studies have reported typical 100–400°C wetted coil temperatures, depending on the device design, flow conditions, voltage, and measurement position relative to the coil [ 10 , 11 , 17 18 ]. Temperatures as high as 1,000°C have been measured for “dry” coils without any e-liquid, so efficient wicking is important for delivering liquid to the coil and maintaining target coil temperatures [ 10 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A variety of nicotine E-cigarette cartridges and pods have been characterized by determining their design components [9], testing their heating coil temperature profiles [10,11], and measuring metal content of their e-liquids and airborne emissions [12][13][14][15][16]. To our knowledge, little comparable information exists in the peer reviewed literature for THC vaping devices [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on e-liquid fill level, coil resistance and voltage settings, the coil temperatures of e-cigarettes ranges from 110 to 1008 °C 11 , 13 . Typical wetted coil temperature is 200–400 °C, extremely high temperatures (around 1000 °C) have been measured for dry coils without any e-liquid 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Densitas (146)(147)(148)(149) 2,61 g/cm 3(150) Titik didih (151)(152)(153)(154) Titik leleh (155)(156)(157)(158) 1.085 °C; 1.985 °F; 1.358 K (dekomposisi) 652 °C; 1.206 °F; 925 K Kelarutan dalam air (159-161) Dalam pelarut lain 0,79 gr/100 mL (20 °C) 1,30 gr/100 mL (80 °C) Larut dalam asam nitrat Tidak larut dalam etanol Struktur kristal (123,162,163) Ortorombik…”
Section: Sifat Kimiaunclassified